2012
DOI: 10.1007/s13224-012-0262-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intrapartum Transcervical Amnioinfusion in Patients with Meconium-Stained Amniotic Fluid

Abstract: Intrapartum transcervical amnioinfusion is valuable in patients with meconium-stained amniotic fluid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…In a study by Bhatia et al in 2013, atonic postpartum hemorrhage occurred more often in the amnioinfusion group (8%) compared with the no amnioinfusion group (2%), though it was not statistically significant (p ¼ 0.217). 16 Our study illustrates similar findings in that amnioinfusion was not associated with increased odds of postpartum hemorrhage compared with intrauterine pressure catheter alone.…”
Section: Discussionsupporting
confidence: 86%
“…In a study by Bhatia et al in 2013, atonic postpartum hemorrhage occurred more often in the amnioinfusion group (8%) compared with the no amnioinfusion group (2%), though it was not statistically significant (p ¼ 0.217). 16 Our study illustrates similar findings in that amnioinfusion was not associated with increased odds of postpartum hemorrhage compared with intrauterine pressure catheter alone.…”
Section: Discussionsupporting
confidence: 86%
“…24 In the present study the incidence of maternal pyrexia in the amnioinfusion group showed a non-significant decrease. While Bhatia et al 12 reported maternal pyrexia did not occur in the amnioinfusion group, but in control group, 6% cases had pyrexia.…”
Section: Discussionmentioning
confidence: 84%
“…[11][12][13][14][15][16] The present study was designed to test the hypothesis that amnioinfusion can reduce the incidence of caesarean deliveries and perinatal morbidity associated with meconium stained amniotic fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Butt & Ahmed (18) reported that transabdominal AI is a useful procedure to reduce complications that result from oligohydramnios as AI increases the latency period, and may result in better perinatal outcome by improving birth weight. Thereafter, Bansal et al (19) found the CS rate due to fetal distress was significantly lower in women of received AI than in controls (20% vs. 40.0 %) and Bhatia et al (20) documented that intrapartum transcervical AI is valuable in patients with MSAF as it significantly increased the chance for having VD with significant reduction of frequency of development of MAS (6% vs. 20%).…”
Section: Results:-mentioning
confidence: 99%
“…Moreover, Bansal et al (19) detected significantly lower frequency of respiratory distress of neonate of women received AI than in control group (4% vs. 12 %). Bhatia et al (20) documented that AI is valuable in patients with MSAF as it provided significant relief from variable decelerations in 68.18% vs. 7.1% in control group, significantly increased the chance for having VD with significant reduction of frequency of development of MAS 6% vs. 20 % in control group. Moreover, multiple literature reviews concluded that AI is associated with substantive improvements in perinatal outcome especially in settings where facilities for perinatal surveillance are limited (12,21) .…”
Section: Results:-mentioning
confidence: 99%